MODEL PEMBELAJARAN LANGSUNG TERHADAP KETERAMPILAN MENULIS KALIMAT DASAR ANAK TUNARUNGU KELAS 1 SDLB-B - Wartanto, Reza (Jurnal Pendidikan Khusus, 2015)
ABSTRACT The Deaf children are the children who are lack or loss of ability to hear. The deaf children are still having trouble in writing, compiling basic sentence structure or SVO (SPO) due to the low of language possessed. The study aims to investigate the effect of direct learning model on the deaf children’s basic sentences writing skill grade 1 SDLB-B Karya Mulia II Surabaya. This research was a quantitative research, with pre-experimental and one group pretest-posttest design. The data was collected using a test to investigate the results of basic sentence writing skill before and after the treatment. The data was analyzed using test formula sign (sign test). The results showed an improvement on the score of basic sentence writing skill. The pretest score was 28.83. It changed to 45 after the posttest. Z table 5% while testing two sides was 1.96. ZH value was 2.05, so that the null hypothesis was rejected and the working hypothesis was accepted. To conclude, “There is a significant effect on the use of direct learning model on The Deaf Children’s Basic Sentence Writing Skill Grade 1 SDLB-B Karya Mulia II Surabaya”.   Keywords: direct learning model, writing a basic sentence